Análisis de la experiencia del trabajo de los resocializadores durante la rehabilitación prestada a adolescentes consumidores de sustancias psicoactivas en Colombia (2020)
The present research has the general objective of analyzing the work experience of resocializers during the rehabilitation provided to adolescents who consume psychoactive substances in Colombia. Methodologically, it is a descriptive research with a documentary design and qualitative approach. The sources of information are represented by guides, manuals, degree works, scientific articles, laws, among other documents that address the problem raised. For data analysis, qualitative analysis was used, using the Atlas.Ti software to relate the words and central ideas most used in the texts under study, using semantic networks, identifying the main categories addressed and, based on this, responding to the planted objectives. It was obtained as a result that the therapeutic role of the resocializers is not limited only to psychological intervention, their functions go further, intervening in all their environment and with the people that the young addict lives, performing a series of key functions to contribute to the improvement of the physical and mental health status of patients who consume psychoactive substances. Identifying that one of the key actions of these social workers is to serve as motivating agents that provide support to young people for the maintenance or incorporation in a series of educational, cultural, training or labor insertion activities, which allow them to actively reintegrate to society